Religion, Politics and Power in Africa: The Nigerian Experiment and Lessons from the Sharī'ah Madīnah Plural Model - Uthman, Ibrahim Olatunde (IAIN Manado, 2023)
This study delves into the complex interplay of religion, politics, and power in Africa, focusing on the Nigerian context and drawing valuable lessons from the Sharīah Madīnah plural model. Through a multidisciplinary approach, including qualitative analysis, case studies, and comparative analysis, the research reveals that Nigeria's political landscape is deeply influenced by religious affiliations, primarily Islam and Christianity, which play pivotal roles in shaping political agendas and power dynamics. The findings underscore the importance of fostering religious tolerance and interfaith dialogue while promoting inclusive governance to navigate the challenges posed by religious diversity in Africa's political systems. Drawing inspiration from the Sharīah Madīnah model, this study advocates for nuanced approaches that respect religious pluralism while upholding democratic principles, offering valuable insights for a more harmonious coexistence in Africa's diverse religious and political milieu.